5‐Fluorouracil – Determination of α‐fluoro‐β‐alanine in urine by GC‐MS/MS [Biomonitoring Methods, 2019]. Issue 1 (30th January 2019) - Schierl, R.; Fischer, E.; Scherer, G.; Hagedorn, H.‐W.; Göen, Th.; Hartwig, A.; ,
Abstract: The working group "Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the presented biomonitoring method. The method described hereinafter permits the determination of α‐fluoro‐β‐alanine (FBAL), the main metabolite of 5‐fluorouracil, at low concentration levels and can be used for the biomonitoring of exposed individuals (manufacture, pharmacy, medicine). To this end, urine samples are spiked with 13 C‐FBAL as internal standard (IS) and acidified with 0.1 M hydrochloric acid. The samples are then extracted and purified using a strong cation exchanger. After resuspension and derivatisation, FBAL is analysed using GC‐MS/MS in the MRM (Multiple Reaction Monitoring) mode and quantified with reference to the internal standard. Calibration standards are prepared in pooled urine and processed in the same way as the samples to be analysed.